(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The Article speaks about historical aspect of mahalla concept. Short mahalla genesis giving on. Carry out critical analysis of mahalla on different days of history. Comparison on mahalla and quarter.